Incidence and risk factors for rectal pain after laparoscopic rectal cancer surgery. (April 2017) - Lee, Jin Young; Kim, Hee Cheol; Huh, Jung Wook; Sim, Woo Seog; Lim, Hyun Young; Lee, Eun Kyung; Park, Hui Gyeong; Bang, Yu Jeong
Objective: This study was performed to investigate the incidence of and potential risk factors for rectal pain after laparoscopic rectal cancer surgery. Methods: We retrospectively analyzed data from 300 patients who underwent laparoscopic rectal cancer surgery. We assessed the presence of rectal pain and categorized patients into Group N (no rectal pain) or Group P (rectal pain). Results: In total, 288 patients were included. Of these patients, 39 (13.5%) reported rectal pain and 14 (4.9%) had rectal pain that persisted for >3 months. Univariate analysis revealed that patients in Group P had more preoperative chemoradiotherapy, more ileostomies, longer operation times, more anastomotic margins of <2 cm from the anal verge, more anastomotic leakage, and longer hospital stays. Multivariate analysis identified an anastomotic margin of <2 cm from the anal verge and a long operation time as risk factors. The presence of diabetes mellitus was a negative predictor of rectal pain. Conclusions: In this study, the incidence of rectal pain after laparoscopic rectal cancer surgery was 13.5%. An anastomotic margin of <2 cm from the anal verge and a long operation time were risk factors for rectal pain. The presence of diabetes mellitus was a negative predictor of rectal pain. Thus, the possibility of postoperative rectal pain should be discussed preoperatively with patients with these risk factors.